EL MUNDO DE AYER, LA COMPRENSIÓN DE NUESTROS LÍMITES Y LA DEPRAVACIÓN DE LAS ÉLITES - Mansilla, H. C. F. (Universidad de Costa Rica, 2022)
The essay tries to detect (and exhibit) some promising and progressive aspects whichwere embodied in the so-called premodern order and in the time previous to theFirst World War. Among those factors we can mention a solid familiar structure,the existence of strong individualities with firm conceptions about the daily sphereof ethics and a high culture, which was still very distant from the actual andextreme relativism of values. That time of classical liberalism was very different incomparison with the actual “volatile capitalism”, which is characterized by selfrefering narcissism and technocratic tendencies. A contribution to the positiveaspects of the world of yesterday was done by an aristocracy (with some premoderntraits), which acknowledged the limits fixed upon us by the natural environment andthe human failures.